Comparing Slope Stability and Validity for General Outcome and Specific Subskill Mastery Measurement. Issue 1 (2nd January 2023) - Filderman, Marissa J.; Barnard-Brak, Lucy
Abstract: Progress monitoring data are central to making informed decisions on intervention intensification for struggling learners. The general outcome measure (GOM) of curriculum-based measurement of oral reading fluency (CBM-R) has been found to correlate with high-stakes assessment; however, data are highly variable, resulting in decisions that must be made 15 weeks after implementation of intervention. Recent researchers have recommended the use of both GOM and specific subskill mastery measurement (SSMM) to overcome the challenges presented with the use of GOM alone, but research on the efficacy of this approach is limited. Using Bayesian and ordinary least squares regression, we compared the GOM of CBM-R with SSMM slopes for words read correctly per minute (wcpm) per week at 5, 7, and 12 weeks, and explored the relation of the respective slopes with subsequent standardized assessment tools for struggling upper elementary students receiving word reading intervention. We found that the SSMM had a similar slope to that noted in prior research (i.e., β = 1.46 wcpm per week). This slope was significant and related to future standardized assessment outcomes across the various time points. The slope for CBM-R was not significant or related to future assessment outcomes. Implications for research and practice are discussed.